(untitled) (Bangladesh Journal of Pharmacology, 2013)
The antipyretic effect of the hydro-methanol extract of Melia azedarach leaves was investigated using the yeast induced pyrexia method in rabbits. Paracetamol was used as a positive control and negative control group received distilled water. Rectal temperatures of all rabbits were recorded immediately before the administration of the extract or vehical or paracetamol and again at 1 h interval for 6 h using digital thermometer. The extract was also phytochemically screened for alkaloids, tannins, saponins, flavonoids, cardiac glycosides and phenols. At 500 mg/kg dose the extract showed significant (p<0.0001) reduction in yeast-induced elevated temperature as compared with that of standard drug paracetamol whereas the extract dose 250 mg/kg was less effective when compared with higher dose (p<0.05). Phytochemical screening showed the presence of alkaloids, tannins, flavonoids, saponins and phenols. This study showed that the hydro-methanol extract of M. azedarach leaves at a dose of 500 mg/kg possesses significant antipyretic effect against the yeast-induced elevated temperature.